Relasi Suami Istri dalam Keluarga menurut Hukum Islam dan Undang-Undang Nomor 1 Tahun 1974 - Fahmi Basyar (Program Pascasarjana Universitas Ibrahimy, 2020)
This study discusses the relationship between husband and wife in the Islamic legal perspective, using qualitative descriptive research methods to obtain valid and factual data. Based on the research results, an analysis of the family relationships is under Islamic law. Decision making in the family as stated in the verse al-quran surah An-Nisa 'verse: 34 and family psychology in general. Meanwhile, the fulfillment of a living is in accordance with the content of the verse al-quran surah Al-Baqarah verse: 233 and the typology in the family psychology they live. Then the implementation of daily household activities is following the contents of the compilation of Islamic law and law number 1 of 1974. Care and protection are the background foundations of aqidah in every family. From the results of this study, it has been concluded that the husband's role as head of the household is constant, while the wife as a housewife has shifted due to the increasing role in the public domain. And regarding the rights and obligations of husband and wife depending on the agreement of both by looking at their daily conditions.